Teachers’ belief on Early Second Language Acquisition in Indonesian Bilingual School - Syafrizal Syafrizal; Tricahyani Endah Yuniarti; Usep Sofyana (Journal of English Language Studies, 2020)
The present study investigated the teachers’ belief in early second language Acquisition.  Participants were 20 teachers who taught in bilingual school in Serang, Indonesia.  The survey was developed by the researcher based on studies on the early second language acquisition.  The result showed that the majority of teachers had beliefs on language transfer and some cognitive effects in second language acquisition. However, the teachers showed the misconception on the belief of a critical period in second language acquisition. These findings provide the additional support to the need of developing the belief among the teachers in second language acquisition.Keywords: Teacher’s belief, Beliefs of Second Language Acquisition, Second Language Acquisition